Northwest History. Alaska. Floods & Flood Control. (1937)
Yukon Over Banks At Eagle, Alaska. Yukon Over Banks At Eagle, Alaska FAIRBANKS, Alaska, Thursday, May 20.—Off)—Flood reports from the Eastern Alaska town of Eagle reached Fairbanks today but conditions at inundated Nenana, on the Tanana River, were improving. Pilot Dick Hawley, flying here from Eagle, said the Yukon overflowed a twenty-foot bank there, leaving water three feet deep in the Northern Commercial Company's store and other waterfront buildings.